Republican conception of liberty in early republican Turkey and its contemporary implications - Erozan, Bogac (Sage Publications Inc, 2016)
Established in 1923, Turkey has been a republic without a dominant republican conception of liberty. A chance to install such a conception was missed in the early republican period and never recaptured. The republic was unable to get rid of vestiges of the authoritarian tradition of the past. Centuries-old authoritarian tradition persisted well into the recent and the contemporary periods. Presenting ample evidence, the article underlines the weight of history and the legacy of authoritarian mentality that promoted the use of authority, not liberty, in political problem-solving. The initial failure to abandon an authoritarian problem-solving approach proved fateful for the chances of the deepening of democracy in Turkey.
Keywords: History; Liberty; Politics; Republicanism; Turkey